Disclosure In Indonesia’s Digital Marketing Regulations: Contract Validity And Consumer Protection - Puspaningtyas Panglipurjati (Sociological Jurisprudence Journal, 2025)
The use of social media in Indonesia continues to grow, not only for social activities but also for economic activities. Deals in economic activities on social media conducted by brands often involve influencers to promote goods or services. This article analyses digital marketing conducted by influencers through social media under Indonesian law. The analysis is performed based on various regulations applicable in Indonesia, such as regulations on electronic commerce and marketing, agreements, and consumer protection, by first looking at rules on digital marketing in various countries. Several countries have more specific regulations, including endorsement guides, emphasizing disclosure obligations and minimum clauses that must be included in contracts between brands and influencers. Contracts between brands and influencers need to be reviewed to ensure that the clauses agreed between the brand and the influencer have an impact on fulfilling the legal requirements of a sales and purchase contract, in this case, relating to a free agreement between the brand and the consumer and by the principles of consumer protection. Based on the review conducted, various existing regulations must be reviewed for their suitability in developing community activities. Further, the urgency of establishing a special regulation on digital marketing conducted by influencers through social media needs to be reviewed.